(untitled) (Journal of Geography and Environmental Management, 2022)
Social tourism in modern conditions requires its development and depends not on the conditions for the development of globalization of the world economy, but on the level of economic development of each country. In this matter, much depends on the support from the state for this type of tourism, such as domestic tourism. Social tourism is one of the most promising sectors of the economy of any state, as it allows, on the one hand, to raise the prestige of any country and ensure its economic development, and on the other hand, it provides healthy recreation for its population. The problems of the development of social tourism in Kazakhstan also depend on the fact that until now a clear state policy has not been developed that allows to really support the development of this type of tourism. The previously developed state programs did not bring the desired result. Until now, all the problems regarding the development of the social tourism industry, protection of the interests of persons participating in this type of activity and using the services of travel companies have not been resolved. This indicates that the state has not yet developed a systematic approach to solving the problems of this industry, since the prospects for the development of social tourism in most cases depend on state policy, state regulation and support of the tourism sector, as well as on the level of economic development in country and in the world.